PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PRODUK INDIHOME PT. TELEKOMUNIKASI INDONESIA - MEREZA .; HERYENZUS . (LP2MTBM MAKARIOZ, 2020)
The development of communication technology in Indonesia is increasingly sophisticated in the lives of people who use itand cannot be avoided. By paying attention to the promotions given to customers and the good quality of products given bythe company to customers so that customer satisfaction is created. This study aims to determine the effect of promotion oncustomer satisfaction, the effect of product quality on customer satisfaction and the effect of promotion and product qualityon customer satisfaction and the object of research is PT Telekomunikasi Indonesia. The test is carried out using the classicassumption test, the influence test and the partial hypothesis test with the t test and simultaneously with the f test. Theresults of the study stated that partially the promotion had a significant effect on customer satisfaction and product qualityhad a significant effect on customer satisfaction and simultaneously promotion and product quality together had a significanteffect on customer satisfaction of PT Telekomunikasi Indonesia products.